A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India - Khan, Mohd Talib; Anis, Shoeba Binte (Zootaxa, 2017)
A new genus and species, Ayaanella globugaster M.T. Khan & Anis gen. nov. and sp. nov. (Hymenoptera: Trichogrammatidae) is described from two females collected in Uttar Pradesh State of India.